The secret of quick thinking: The invention of mental speed in America, 1890–1925 - Clark, Justin Tyler (Time & society, 2020)
In the early 20th century, mental speed became a dominant measure of intelligence in the United States. For both cultural and technical reasons, this had not always been the case. For 19th-century Americans, quickness of speech and thought often signified lack of self-discipline. Unlike with other objects of temporal measurement and rationalization such as factory work, little scientific or popular consensus existed over how to clock the invisible phenomenon of thought. The cultural and scientific ascent of mental speed thus poses an unsolved historical problem: how and why did Americans adopt this new ideal of intelligence? This essay offers an answer in the introduction and popularization of a new and controversial practice: the timed test. The first timed tests did not so much formalize an existing conception of mental efficiency as establish a new one, using one of the key tools of measurement available to experimental psychology, the mechanical time-keeper. Initially frustrated in their efforts to correlate their subjects' laboratory-measured reaction time with socially recognized achievements such as academic grades, psychologists in the late 1890s borrowed a still-obscure concept from stenography and telegraphy: words per minute. At first, few scientists or members of the public equated reading, speaking, writing, and listening rate with intelligence. Only after American educators, military recruiters, and vocational guidance experts began to adopt timed testing in the 1910s for administrative convenience did mental speed begin to indicate intelligence and knowledge. What began as a way to test minds efficiently evolved almost inadvertently into a test of their efficiency.